Analisis Persepsi Mahasiswa Terhadap Praktikum Pembuatan Biodiesel Minyak Jelantah Berbasis Low-cost equipment - Sayekti, Titah; Rokmana, Arinta Windiyanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The growing dependence on fossil fuels has triggered environmental concerns, including greenhouse gas emissions and air pollution. Biodiesel production from waste cooking oil offers an environmentally friendly alternative that can be implemented through practical science activities. However, limited laboratory facilities often hinder its application in higher education. This study aims to analyze students’ perceptions of a biodiesel production experiment using low-cost equipment. A mixed-method approach with a sequential explanatory design was employed. Quantitative data were collected through closed-ended questionnaires completed by 63 students from the “Energy in Life Systems” course, complemented by semi-structured interviews with 10 selected participants. The five dimensions assessed included conceptual understanding, ease of use, safety, engagement, and cost-efficiency. Results showed mean scores of 4.46 for conceptual understanding (very good), 4.37 for cost-efficiency (very good), 4.43 for safety (very good), 4.46 for engagement (very good), and 4.06 for ease of use (good). Qualitative findings reinforced that students found the practicum effective, safe, enjoyable, and aligned with real-world applications. In conclusion, the use of low-cost equipment in biodiesel practicum enhances meaningful and contextual science learning, especially in resource-limited educational settings. Therefore, low-cost equipment-based practicum is recommended to be integrated into the science education curriculum, particularly in the context of project-based learning and limited laboratory facilities. Key Words: biodiesel; low-cost equipment; practical learning; student perception; renewable energy